Short-time mentoring – enhancing female medical students’ intentions toward surgical careers - J. C. Mossanen; M. Schmidt; A. Brücken; M. Thommes; G. Marx; S. Sopka (Medical Education Online)
Background Women pursuing a career in surgery or related disciplines are still in the minority, despite the fact that women compose at least half of the medical student population in most Western countries. Thus, recruiting and retaining female surgeons remains an important challenge to meet the need for surgeons and increase the quality of care. The participations were female medical students between their third and fifth academic year. In this study, we applied the well-established psychological theory of planned behavior (TPB) which suggests that the intention to perform a behavior (e.g. pursuing a career in surgery) is the most critical and immediate predictor of performing the behavior. We investigated whether a two-part short-mentoring seminar significantly increases students’ intention to pursue a career in a surgical or related specialty after graduation.Method The mentoring and role-model seminar was conducted at 2 days for 90 minutes by six inspiring female role models with a remarkable career in surgical or related disciplines. Participants (N = 57) filled in an online survey before (T0) and after the seminar (T1). A pre-post comparison of central TPB concept attitude towards the behavior, 2) occupational self-efficacy and 3) social norm) was conducted using a paired sampled t-test. A follow-up survey was administered 12 months later (T2).Results The mentoring seminar positively impacted female students’ attitude towards a career in a surgical specialty. Female students reported a significantly increased positive attitude (p < .001) and significantly higher self-efficacy expectations (p < .001) towards a surgical career after participating in the mentoring seminar. Regarding their career intention after the seminar, female students declared a significantly higher intention to pursue a career in a surgical specialty after graduating (p < .001) and this effect seems to be sustainable after 1 year.Conclusion For the first time we could show that short-mentoring and demonstrating role models in a seminar surrounding has a significant impact on female medical student decision´s to pursue a career in a surgery speciality. This concept may be a practical and efficient concept to refine the gender disparity in surgery and related disciplines.